2008
DOI: 10.1002/sim.3405
|View full text |Cite
|
Sign up to set email alerts
|

A class comparison method with filtering‐enhanced variable selection for high‐dimensional data sets

Abstract: High-throughput molecular analysis technologies can produce thousands of measurements for each of the assayed samples. A common scientific question is to identify the variables whose distributions differ between some pre-specified classes (i.e., are differentially expressed). The statistical cost of examining thousands of variables is related to the risk of identifying many variables that truly are not differentially expressed, and many different multiple testing strategies have been used for the analysis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the microarray literature, several authors have suggested filtering to reduce the impact that multiple testing adjustment has on detection power (7)(8)(9)(10)(11)(12). Conceptually similar screening approaches have also been proposed for variable selection in high-dimensional regression models (13,14).…”
mentioning
confidence: 99%
“…In the microarray literature, several authors have suggested filtering to reduce the impact that multiple testing adjustment has on detection power (7)(8)(9)(10)(11)(12). Conceptually similar screening approaches have also been proposed for variable selection in high-dimensional regression models (13,14).…”
mentioning
confidence: 99%
“…If we are to relate these high-dimensional features to some outcome variable in a regression set-up, we need to perform some sort of variable selection. 14…”
Section: Introductionmentioning
confidence: 99%
“…If we are to relate these high-dimensional features to some outcome variable in a regression set-up, we need to perform some sort of variable selection. [1][2][3][4] The most commonly used method for identifying important predictor variables in a high-dimensional regression model is to fit a penalized model. Consider the linear regression model with response variable Y and p explanatory variables (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of weighted hypothesis testing can be found in [27] and the references therein. A different approach, based on a two-stage approach mainly arising from the microarray literature [6,16,24,25,33,34], extracted the prior information to remove a subset of genes which seem to generate uninformative signals in the filtering stage, followed by applying some multiple testing procedure to the remaining genes which have passed the filter in the selection stage.…”
mentioning
confidence: 99%